2018
DOI: 10.1016/j.jid.2018.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Platelet-Activating Factor Synthesis Facilitates Acute and Delayed Effects of Ethanol-Intoxicated Thermal Burn Injury

Abstract: Thermal burn injuries in patients who are alcohol-intoxicated result in greater morbidity and mortality. Murine models combining ethanol and localized thermal burn injury reproduce the systemic toxicity seen in human subjects, which consists of both acute systemic cytokine production with multiple organ dysfunction, as well as a delayed systemic immunosuppression. However, the exact mechanisms for these acute and delayed effects are unclear. These studies sought to define the role of the lipid mediator platele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(41 citation statements)
references
References 55 publications
(129 reference statements)
3
38
0
Order By: Relevance
“…Of interest, structural analysis of PAF-R agonistic activity following the combination of EtOH þ UVB in HaCaT cells by mass spectrometric analysis revealed only enzymatically generated PAF agonists 1-hexadecyl-2-acetyl GPC and 1-octadecyl-2-acetyl GPC, not significant amounts of oxidized GPCs (data not shown), which we have described are generated following higher fluences of UVB (Marathe et al, 2005). Previously, we have demonstrated that topical application of 20% EtOH to de-identified discarded human skin explants derived from surgical contouring procedures (exempted study, Wright State University) 30 minutes before a thermal burn injury results in an augmentation of PAF production (Harrison et al, 2018). Using this protocol, we tested whether topical EtOH pretreatment can increase PAF following UVB treatment.…”
Section: Supplementary Materialsmentioning
confidence: 56%
See 3 more Smart Citations
“…Of interest, structural analysis of PAF-R agonistic activity following the combination of EtOH þ UVB in HaCaT cells by mass spectrometric analysis revealed only enzymatically generated PAF agonists 1-hexadecyl-2-acetyl GPC and 1-octadecyl-2-acetyl GPC, not significant amounts of oxidized GPCs (data not shown), which we have described are generated following higher fluences of UVB (Marathe et al, 2005). Previously, we have demonstrated that topical application of 20% EtOH to de-identified discarded human skin explants derived from surgical contouring procedures (exempted study, Wright State University) 30 minutes before a thermal burn injury results in an augmentation of PAF production (Harrison et al, 2018). Using this protocol, we tested whether topical EtOH pretreatment can increase PAF following UVB treatment.…”
Section: Supplementary Materialsmentioning
confidence: 56%
“…Recently, our group demonstrated that ethanol (EtOH) exposure results in an augmentation of enzymatic PAF synthesis in response to thermal burn injury, in a process involving cytosolic phospholipase A 2 (Harrison et al, 2018). The present study was designed to test the hypothesis that EtOH exposure could generate increased levels of PAF in response to UVB, and that UVB will be more immunosuppressive when EtOH intoxicated.…”
Section: Supplementary Materialsmentioning
confidence: 97%
See 2 more Smart Citations
“…Of interest, melanocytes, skin fibroblasts, and T cells do not, yet B cells express PAFRs ( 34 , 115 , 116 ). Elevated PAFR agonist levels can be detected following multiple pathophysiologic stressors ranging from burn injury to X-radiation ( 41 , 117 , 118 ). Moreover, PAF can be detected in cold urticaria ( 119 ), immunobullous diseases such as bullous pemphigoid ( 120 ), following sunburn ( 121 ), and in the skin disease psoriasis ( 122 ).…”
Section: Paf and Uvb Radiationmentioning
confidence: 99%